G*E interaction of 135 recombinant inbred lines of sorghum for biofuel production - Rodríguez García, Armando; Zamora Villa, Víctor Manuel; Reyes Valdés, Manuel Humberto; Villarreal Quintanilla, José Ángel; Rodríguez Herrera, Raúl; Aguilar González, Cristóbal (Revista Mexicana de Ciencias Agrícolas, 2018)
Sorghum (Sorghum bicolor (L) Moench) is one of the main basic foods for the poorest people in the world, suffering from a situation of increased food insecurity. This crop is adapted to a warmer and drier agro-ecological environment, where it ́s difficult to grow other cereals. The formation of outstanding genotypes requires to evaluating the genetic materials in different environments and determines their genotype- environment interaction. The objective was to detect and analyze the genotype-environment of a group of recombinant inbred lines and select the highest potential to be used in the production of biofuels. 135 recombinant inbred lines of sorghum were evaluated at different locations during the years 2006, 2007 and 2008. Data from seven variables were analyzed as corresponding to an experiment in randomized block design in each of several environments. Genotype-environment interaction was analyzed using theAMMI model. It was highly significant, scoring the recombinant inbred lines, selecting them by its size and selecting those with less magnitude, the best environment for the proper development of recombinant inbred lines were determined and, 13 lines with higher sugar content were selected measured in °Bx.
Keywords: Sorghum bicolor L. Moench; environments; sugar content; genotype; outstanding